IMPLEMENTATION OF DIGITAL TRANSFORMATION TO IMPROVE THE QUALITY OF LAND SERVICES - Lulus Yuswardono Prasetyanto; Sudarmo; Rino Ardhian Nugroho (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Digital transformation at the National Land Agency (BPN) is a strategic response to demands for faster, more transparent, and accountable public services. This study aims to identify the forms of digital transformation that have been implemented and the challenges faced in their implementation. The method used was a literature review of ten relevant recent scientific journals. The results show that the BPN's digital transformation includes electronic land certificates, electronic mortgages, the Touch My Land public service application, land archive digitization, strengthening the digital competence of civil servants (ASN), an electronic queuing system, and service integration with Land Deed Officials (PPAT). Despite significant progress, challenges such as infrastructure, digital literacy, and inter-agency coordination remain obstacles. This study concludes that the success of the BPN's digital transformation requires a holistic approach encompassing technology, human resources, and supporting regulations.